Associative memory based image and object recognition by quantum holography - Loo, C.K.; PeruÅ¡, M.; Bischof, H. (2004)
A quantum associative memory, much more natural than those of quantum computers, is presented. Neural-net-like processing with real-valued variables is transformed into processing with quantum waves. Successful computer simulations of image storage and retrieval are reported. Our Hopfield-like algorithm allows quantum implementation with holographic procedure using present-day quantum-optics techniques. This brings many advantages over classical Hopfield neural nets and quantum computers with logic gates.